Śmierć jako przejście do trzeciej fazy życia człowieka w myśli Gustava Theodora Fechnera - Bohdanowicz, Andrzej (Teologia i Moralność, 2017)
Although dying as the last act of life constitutes part of our earthly existence, death is difficult to accept. Faced with death an individual has always started asking questions about the meaningfulness of his/ her life and life after death. In the contemporary western culture characterized among others by the collapse of the social structures, people very rarely die surrounded by their families as they used to do, but in hospitals, i.e. in isolation, suffering from loneliness, connected to a range of technologically advanced medical devices. Socio-cultural changes have brought about a conviction that death ends human existence. Catholic faith, however, offers hope that death provides access to desirable future events. As a pass-through state death is the end and the beginning, since after death life is transformed. Consequently, we die trustfully hoping to be rewarded with eternal life.